Optical Microelectromechanical Systems Technologies for Spectrally Adaptive Sensing and Imaging. (12th September 2021) - Martyniuk, Mariusz; Silva, K. K. M. B. Dilusha; Putrino, Gino; Kala, Hemendra; Tripathi, Dhirendra Kumar; Singh Gill, Gurpreet; Faraone, Lorenzo
Abstract: Evolving from past black‐and‐white images, through present red‐green‐blue spectral colors, future remote imaging systems promise spectroscopic functionalities extending well beyond the visible wavelengths. This allows real‐time spectral information to be gathered from multiple wavelength bands that is applicable to numerous remote sensing spectroscopy/imaging applications and aids target recognition. This paper reviews the wavelength tunable microelectromechanical systems (MEMS) optical filter technologies developed for the important infrared and the emerging terahertz wavelength bands of the electromagnetic spectrum with the fabrication effort being enabled by the Western Australian Node of the Australian National Fabrication Facility. A low size, weight and power (SWaP) platform solution is demonstrated delivering mechanically robust, field‐portable, spectroscopic, chem/bio sensing suitable for deployment in remote sensing and imaging applications. Abstract : This review presents wavelength tunable microelectromechanical systems (MEMS) optical filter technologies for the important infrared and the emerging terahertz wavelength bands of the electromagnetic spectrum with the fabrication effort being enabled by the Western Australian Node of ANFF. A low size, weight and power (SWaP) solution is demonstrated, delivering mechanically robust spectrally selective sensing suitable for deployment on field‐portable platforms being increasingly demanded for remote sensing and imaging.